Development of a novel set of Gateway-compatible vectors for live imaging in insect cells - Maroniche, Guillermo Andrés; Mongelli, Vanesa Claudia; Alfonso, Victoria; Llauger, Gabriela; Taboga, Oscar Alberto; Del Vas, Mariana (The Royal Entomological Society, 2023)
Insect genomics is a growing area of research. To exploit fully the genomic data that are being generated, high-throughput systems for the functional characterization of insect proteins and their interactomes are required. In this work, a Gateway-compatible vector set for expression of fluorescent fusion proteins in insect cells was developed. The vector set was designed to express a protein of interest fused to any of four different fluorescent proteins [green fluorescent protein (GFP), cyan fluorescent protein (CFP), yellow fluorescent protein (YFP) and mCherry] by either the C-terminal or the N-terminal ends. Additionally, a collection of organelle-specific fluorescent markers was assembled for colocalization with fluorescent recombinant proteins of interest. Moreover, the vector set was proven to be suitable for simultaneously detecting up to three proteins by multiple labelling. The use of the vector set was exemplified by defining the subcellular distribution of Mal de Río Cuarto virus (MRCV) outer coat protein P10 and by analysing the in vivo self-interaction of the MRCV viroplasm matrix protein P9-1 in Förster resonance energy transfer (FRET) experiments. In conclusion, we have developed a valuable tool for high-throughput studies of protein subcellular localization that will aid in the elucidation of the function of newly described insect and virus proteins.